Problematika Dan Strategi Dalam Pembelajaran Bahasa Indonesia Pada Kelas Satu Sekolah Dasar - Elyvia Widyaswarani (Journal of Innovative and Creativity, 2025)
Learning Indonesian often encounters problems in its implementation, especially in the implementation of learning Indonesian in first grade. This study aims to find out what problems occur in learning Indonesian in first grade and what strategies the class teacher applies to overcome these problems. This study used qualitative research methods. Data collection techniques in this study are observation, interviews, and documentation. Data collection in this study was carried out in April-May 2025. This research was carried out at SDIT Tunas Bangsa Banjarnegara with participants in this study including grade 1 teachers as interviewees. The results showed that the problems faced by students in learning included easy loss of focus and concentration, difficulty using Indonesian properly and correctly, difficulty reading and writing.